Analisis Bibliometrik dari Penelitian Bank Sampah untuk Pengelolaan Persampahan : 2008 - 2018 (Bibliometric Analysis of Waste Bank Research for Solid Waste Management: 2008 – 2018) - Laili Fitria; Ulli Kadaria (Jurnal Teknologi Lingkungan Lahan Basah, 2019)
Abstract The concept of waste management through a waste bank was first researched in Thailand in 2008. It is known that waste banks can minimize the volume of waste that will be disposed of to landfill. Waste banks also create economic opportunities and can improve the quality of the environment. This research was conducted to find out how to manage waste through a waste bank. Scientific articles indexed by Dimensions (2008-2018) were analyzed by the systematic library review (SLR) method. The parameters analyzed include aspects of the number of articles published, journal choice, article writer, author's institution and country of origin, author collaboration, and the number of citations. The results of the analysis are visualized with the VOSviewer application. There are 99 scientific articles known and can be known by authors, institutions and any country in the world that study waste banks for waste management. Publications on waste banks tend to experience a significant increase from 2016 to 2018. Popular research topics are community-based waste management, changes in environmental care behavior, and performance evaluation and success factors for waste banks. Keywords: bibliometric, systematic literature review, VOSviewer, waste bank Abstrak Konsep pengelolaan sampah melalui bank sampah pertama kali diteliti di Thailand pada tahun 2008. Diketahui bahwa bank sampah bisa meminimalkan volume limbah yang akan dibuang ke TPA. Bank sampah juga menciptakan peluang ekonomi dan bisa meningkatkan kualitas lingkungan. Penelitian ini dilakukan untuk mengetahui bagaimana pengelolaan sampah melalui bank sampah. Artikel ilmiah yang terindeks Dimensions (2008-2018) dianalisis dengan metode tinjauan pustaka sistematis (SLR). Parameter yang dianalisis meliputi aspek jumlah artikel yang terbit, pilihan jurnal, penulis artikel, institusi penulis serta asal negara, kolaborasi penulis, dan jumlah kutipan. Hasil analisa tersebut divisualisasikan dengan aplikasi VOSviewer. Diketahui ada 99 artikel ilmiah dan bisa diketahui penulis, institusi dan negara mana saja di dunia yang meneliti mengenai bank sampah dalam pengelolaan sampah. Publikasi mengenai bank sampah cenderung mengalami peningkatan yang signifikan dari tahun 2016 hingga 2018. Topik popular penelitian adalah manajemen pengelolaan sampah berbasis masyarakat, perubahan perilaku peduli lingkungan, serta evaluasi kinerja dan faktor keberhasilan bank sampah.   Kata kunci: bank sampah, bibliometrik, tinjauan pustaka sistematis, VOSviewer.